The Effects of Different Exercise Modalities in Alzheimer's Disease - ÖZBEYLİ, DİLEK; KASIMAY ÇAKIR, ÖZGÜR (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease and the most common cause of dementia. Increased oxidative stress, abnormal amyloid beta (A beta) accumulation, tau aggregation, neuroinflammation, neuronal plasticity failure, and neuronal loss are the main factors related to the pathophysiology of AD. Increasing evidence suggests that physical activity has a positive effect on both cognitive function and cellular pathologies of AD. It has been demonstrated that aerobic exercise (AE) increases the activity of antioxidant enzymes and synthesis of neurotrophic factors, decreases the levels of neuroinflammatory markers, and enhances the functions of learning and memory. It is also beneficial for the improvement of cell survival and upregulation of A beta clearance. AE has been shown to reduce the levels of soluble A beta(1-42) via an increase in enzyme activity, which is responsible for the upregulation of A beta clearance in brain tissues. It also represses apoptotic cascades such as the caspase-9, cytochrome c, Bax, and caspase-3 cascades. Although there are no clear data on the effects of resistance exercise (RE) on AD, only a small number of articles have studied the effects of RE on models of aging. In these studies, RE increased the serum concentrations of insulin-like growth factor-1 and brain-derived neurotrophic factor (BDNF), reduced oxidative stress in humans, and up-regulated the hippocampal expression of BDNF mRNA in animals. In addition, RE and AE therapies may help progress in daily activities and enhance physical ability in AD patients. Eventually, exercise therapy regimens may lead to more effective treatment options and slow the progression of AD without any side effects.
Keywords: Alzheimer's disease; exercise therapy; antioxidant enzymes; neuronal plasticity; PHYSICAL-EXERCISE; MOUSE MODEL; COGNITIVE FUNCTION; HIPPOCAMPAL NEUROGENESIS; RESISTANCE EXERCISE; VOLUNTARY; MEMORY; ADULT; BETA; BIOMARKERS